Steel Structures Research Update: Seismic Performance of Nonorthogonal Special Moment Frame Beam-to-Column Connections - Liu, Judy (Engineering Journal, 2021)
Ongoing research on the seismic behavior of nonorthogonal special moment frame beam-to-column connections is highlighted. Featured is a comprehensive experimental and computational study under way at the University of Arkansas and led by Dr. Gary Prinz, Associate Professor in Structural Engineering. The research team includes PhD students Hossein Kashefizadeh and Damaso Dominguez. Dr. Prinz’s research interests include mechanics and simulation of ductile fracture, seismic design solutions for steel structures, and computer simulation of structures under dynamic loading. He received a National Science Foundation Faculty Early Career Development (CAREER) award to investigate a new micromechanics-based approach to ductile fracture simulation in additively manufactured steels for improved seismic structural fuse design. Dr. Prinz has also been awarded AISC’s Milek Fellowship. The four-year Milek Fellowship is supporting this research on the seismic performance of skewed special moment frame (SMF) connections. The research team is partway through the third year of the four-year study. Selected results from the computational parametric study are highlighted along with a preview of the experimental investigation.